Mafia Peradilan Indonesia - ardi maulidin; Dadang Suprijatna; Zahra Salsabila Putri; Maya Indhira; Wanda Fasha Pertiwi; Dwi Setiawati (Fakultas Hukum Universitas Djuanda, 2022)
Corruption is an act that is against the law and is detrimental both in social life and in the life of the state. Corruption is often said to be an Extraordinary Crime or a crime that has an extraordinary impact on the running of the government process in a country. In Indonesia, there are also rampant cases of corruption committed by law enforcers, namely the judicial mafia. The existence of the Judicial Mafia is a real form of Corruption Crime in the world of justice by abusing the authority they have. This unlawful act committed by the Judicial Mafia can affect the law enforcement process so that certainty and justice in the law are not achieved, and can damage the justice system in Indonesia. Method: this research is a normative juridical research, namely a research with the approach of laws and regulations, theory, and doctrine, as well as other relevant documents. Results: Several factors have contributed to the growing corruption in Indonesia, namely: (1) Conditions of laws and regulations. (2) Lack of legal awareness in society. (3) Judges have very strong powers and authorities. (4) Lack of Law Enforcement Officials' morale.